2020
DOI: 10.1084/jem.20192378
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal restriction of endothelial cell calcium signaling is required during leukocyte transmigration

Abstract: Endothelial cell calcium flux is critical for leukocyte transendothelial migration (TEM), which in turn is essential for the inflammatory response. Intravital microscopy of endothelial cell calcium dynamics reveals that calcium increases locally and transiently around the transmigration pore during TEM. Endothelial calmodulin (CaM), a key calcium signaling protein, interacts with the IQ domain of IQGAP1, which is localized to endothelial junctions and is required for TEM. In the presence of calcium, CaM binds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Here, we present results that are consistent with this observation. Leukocyte transendothelial migration occurs in the micron-sized spaces in the venules of the specific capillaries produced by migrating white blood cells 22 and is closely associated with the inflammatory response, multiple sclerosis and other regulatory abnormalities 23 , 24 . However, there is no evidence that the differentially expressed CNV genes GNA12, MYL12A, and MYL12B in leukocyte transendothelial migration are significantly correlated with occult LNM, and the underlying mechanism needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we present results that are consistent with this observation. Leukocyte transendothelial migration occurs in the micron-sized spaces in the venules of the specific capillaries produced by migrating white blood cells 22 and is closely associated with the inflammatory response, multiple sclerosis and other regulatory abnormalities 23 , 24 . However, there is no evidence that the differentially expressed CNV genes GNA12, MYL12A, and MYL12B in leukocyte transendothelial migration are significantly correlated with occult LNM, and the underlying mechanism needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium itself is not passive during this process and can be regulated via signaling molecules like vascular endothelium protein tyrosine phosphatase, which, in turn, regulates the integrity of endothelial cell junctions and the subsequent ability of cells to exit the vasculature (Drexler et al, 2019). Moreover, recent work has demonstrated that local endothelial cell calcium fluxes triggered by migrating cells are important for transmigration because blocking calcium signaling in the endothelium severely disrupts transendothelial migration (Dalal et al, 2021). Lipid mediators, in addition to chemokines and cytokines, sus-tain neutrophil polarization and adhesion via a LTB4-BLT1 axis, forming another important arm of regulation during extravasation (Saha et al, 2017;Subramanian et al, 2020).…”
Section: Neutrophil Adhesion and Migrationmentioning
confidence: 99%
“…Despite all innovations, it remains unclear whether the progress made in RNAi technology to date is sufficient to develop a successful CaMKIIδ-directed therapy. Apart from cardiomyocytes, CaMKIIδ is also the dominant isoform in smooth muscle cells ( House et al, 2007 ) and endothelial cells ( Wang et al, 2010 ; McCluskey et al, 2019 ; Dalal et al, 2021 ), so differences in cellular function need to be investigated to predict and avoid potential side effects. In general, it is important to further investigate the precise role of the different splice isoforms of CaMKIIδ, because the complex and diverse involvement of CaMKIIδ in various cellular and intracellular processes will require precise fine-tuning of therapeutics.…”
Section: Antisense Oligonucleotides Targeting Camkiiδmentioning
confidence: 99%